The year's best science fiction & fantasy - Horton, Rich (Prime Books, 2016)
This eighth volume of the year's best science fiction and fantasy features over thirty stories by some of the genre's greatest authors, including John Barnes, Elizabeth Bear, C.C. Finlay, Yoon Ha Lee, Kelly Link, Ian McDonald, Seanan McGuire, Vonda N. McIntyre, Geoff Ryman, Catherynne M. Valente, Genevieve Valentine, and many others. Selecting the best fiction from periodicals including Analog, Asimov's, Clarkesworld, Lightspeed) as well as top anthologies (Meeting Infinity, Old Venus, Operation Arcana, Stories for Chip) and other venues, The Year's Best Science Fiction & Fantasy is your guide to magical realms and worlds beyond tomorrow.